If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(5 + -3y) = 7y + 25 (5 * -4 + -3y * -4) = 7y + 25 (-20 + 12y) = 7y + 25 Reorder the terms: -20 + 12y = 25 + 7y Solving -20 + 12y = 25 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. -20 + 12y + -7y = 25 + 7y + -7y Combine like terms: 12y + -7y = 5y -20 + 5y = 25 + 7y + -7y Combine like terms: 7y + -7y = 0 -20 + 5y = 25 + 0 -20 + 5y = 25 Add '20' to each side of the equation. -20 + 20 + 5y = 25 + 20 Combine like terms: -20 + 20 = 0 0 + 5y = 25 + 20 5y = 25 + 20 Combine like terms: 25 + 20 = 45 5y = 45 Divide each side by '5'. y = 9 Simplifying y = 9
| -(2x-1)=3 | | -77=-7(n+6) | | 6x-2x-10=18 | | 6x-24=5x+25 | | 7+3x=-x+23 | | 0.125(n-0.8)=-0.5(n-0.8) | | 4p^2-8p-194=-2 | | 5x^2-4x-20=2x+2 | | .12+3x=24 | | 12x^2-24x=-4x | | M^2-2M-3=5 | | 16+12x=100 | | 6x+17=5(2x+1) | | 6r^2=-6r+36 | | 4x^2-392=0 | | 0=x^2-14x+3 | | 9p-8p=-4+10 | | 0.25v-0.43=0.29v-0.25 | | (K-2)(K+7)=0 | | X+3x-13=19 | | 10n^2-36=-18n | | g+14=352 | | -17-1+26-35=-4-4m-9+5m | | 2x^2-8x+1=3x+7 | | 5x-1+9x+41+11x+21+x+39=360 | | -3+10=y-1 | | -14+3x=x+14 | | 7(7x+8)+8=49x+64 | | 4p^2-8p-194=0 | | -3(c+3)=3 | | 797x+80+8=49x+64 | | r-39=-33 |